2019
DOI: 10.21203/rs.2.10030/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Convergent degeneration of olfactory receptor gene repertoires in marine mammals

Abstract: Background: Olfactory receptors (ORs) can bind odor molecules and play a crucial role in odor sensation. Due to the frequent gains and losses of genes during evolution, the number of OR members varies greatly among different species. However, whether the extent of gene gains/losses varies between marine mammals and related terrestrial mammals has not been clarified, and the factors that might underlie these variations are unknown. Results: To address these questions, we identified more than 10,000 members of t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…olfactory bulb and cribriform plate, two components of olfaction, compared to their terrestrial relatives (24)(25)(26). Aquatic vertebrates also have a smaller repertoire of functional olfactory receptor (OR) genes than terrestrial vertebrates (27)(28)(29)(30)(31)(32). Nevertheless, how pervasive, consistent, and strong these putative convergences and trade-offs are remains unknown.…”
Section: Significancementioning
confidence: 99%
“…olfactory bulb and cribriform plate, two components of olfaction, compared to their terrestrial relatives (24)(25)(26). Aquatic vertebrates also have a smaller repertoire of functional olfactory receptor (OR) genes than terrestrial vertebrates (27)(28)(29)(30)(31)(32). Nevertheless, how pervasive, consistent, and strong these putative convergences and trade-offs are remains unknown.…”
Section: Significancementioning
confidence: 99%
“…This obvious change of HoxC gene is potentially caused by two rounds of genome-wide replication in early vertebrates (Damas et al, 2018;Venkatesh et al, 2014), as one of the duplicated homologous regions occurred a large number of gene deletions, maintained the status consistent with early vertebrate differentiation. In previous research, vertebrate OR genes can be classified into two types, which are further classified to 11 groups (Figure 7, α-λ) corresponding to the 11 ancestral OR genes of the most common recent ancestor among vertebrate species (Freitag et al, 1998;Gaillard et al, 2004;Liu et al, 2019a;Niimura and Nei, 2005). We identified the OR genes in 62 representative aquatic and terrestrial species, where Amphibia species (such as xenopus and axolotl) possessed approximately 1000 OR genes in the genome, which is much more than other species.…”
Section: Key Gene Families Involved In Water-land Transitionsmentioning
confidence: 99%
“…However, they lack the dorsal domain of the olfactory bulb, an area known to induce innate avoidance behavior against odors of predators and spoiled foods (Kishida, Thewissen, Hayakawa, Imai, & Agata, 2015). The number of genes coding for the olfactory receptors (OR), i.e., the sensory receptors of the main olfactory system, is low in this taxonomic group compared to their close terrestrial relatives (Kishida et al, 2015;Liu et al, 2019). However, the proportion of OR pseudogenes varies greatly among different species, with some having about 65% of their OR genes still functional (Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The number of genes coding for the olfactory receptors (OR), i.e., the sensory receptors of the main olfactory system, is low in this taxonomic group compared to their close terrestrial relatives (Kishida et al, 2015;Liu et al, 2019). However, the proportion of OR pseudogenes varies greatly among different species, with some having about 65% of their OR genes still functional (Liu et al, 2019). Several authors have thus suggested they could use chemicals such as DMS as long-distance cues while foraging or navigating in the pelagic environment (Drake et al, 2015;Hagelin, Straley, Nielson, & Szabo, 2012;Thewissen et al, 2011;Torres, 2017).…”
Section: Introductionmentioning
confidence: 99%